Familial Dysautonomia, Report of 3 Cases from Iran and a Discussion about Their General and Anaesthesia Care - Radpay, Badiozaman; Poor Zamany Nejat Kermany, Mahtab; Halimi-Asl, Ali Asghar (Novelty in Biomedicine, 2015)
Background: Familial Dysautonomia (FD) is a rare hereditary syndrome which is an autosomal recessive trait that typically affects Jewish children. Important signs and symptoms of the disorder include; diminished pain perception, absence of overflow tears, hypotonia, fainting cardiac arrhythmias and autonomic crisis. Cases Report: In this article we reported 3 cases of FD syndrome which had presented for surgical operation followed by a discussion about general care of these patients as well as Anesthesia considerations.